Tests of no cross-sectional error dependence in panel quantile regressions - Matei Demetrescu; Mehdi Hosseinkouchack; Paulo M. M. Rodrigues (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
This paper argues that cross-sectional dependence (CSD) is an indicator of misspecification in panel quantile regression (QR) rather than just a nuisance that may be accounted for with panel-robust standard errors. This motivates the development of a novel test for panel QR misspecification based on detecting CSD. The test possesses a standard normal limiting distribution under joint N, T asymptotics with restrictions on the relative rate at which N and T go to infinity. A finitesample correction improves the applicability of the test for panels with larger N. An empirical application to housing markets illustrates the use of the proposed cross-sectional dependence test.
Keywords: C12; C23; 330; Cross-unit correlation; conditional quantile; factor model; exogeneity